Impact of an interface electrode charge and materials polarization to a conductive interface crack. (September 2022) - Loboda, V.; Sheveleva, A.; Chapelle, F.; Lapusta, Y.
Highlights: A crack and an electrically charged electrode at the interface are considered. Piezoelectric bimaterial with arbitrary direction of polarization is studied. The combined Dirichlet-Riemann problem is formulated and solved analytically. The impact of the electrode charge and the materials' polarization direction is shown. The way of mitigating of the threat of crack propagation is suggested. Abstract: A charged interface electrode and a conductive interface crack between different piezoelectric half-spaces with an arbitrary polarization direction under out-of-plane mechanical loading and in-plane electrical field are considered. An analytical method is used based upon the presentations of the electromechanical characteristics through sectionally-analytic vector-functions with the following formulation and solution of the combined Dirichlet-Riemann boundary value problem. Special attention is devoted to the formulation of the Gauss theorem for the electrode, which permits to take into account its charge. The expressions for stress, electric field, electric displacement jumps and the energy release rate (ERR) are found in a simple analytical form. The numerical results show the dependence of the ERR on the electrode charge, on the intensity of the electric field and on the directions of the polarization of the piezoelectric materials. It is particularly found that due to the appropriate choice of these parameters, the maximum value of the ERR for the crack can be substantially reduced, which mitigates the threat of crack propagation.